THE EFFECTS OF ORGANIZATION CULTURE, LEADERSHIP AND JOB MOTIVATION UPON THE EMPLOYEES PERFORMANCE (Study at PT. PLN Educational and Training Center at Pasar Minggu, Jakarta Selatan) - Sumardjono Jono (STIE Binaniaga, 2017)
The research consists of several steps that must be met in order to achieve results that meet the rules o fscientific research.Results of this study is expected to get ideas of the effect of the employee's performance by organizational culture, leadership and motivation to work at PT.PLN (Persero) Education and Training Centre.The method used is quantitative method which examines four variables: three independent variables and one dependent variabel.The hypothesis testing at the 0.05 level with a population of more than 115 employees, the operational level.The result is that there is a direct effect of organizational culture on the performance of β41 = 0,459 with value tcalculate = 5,354 and ttable (α = 0,05) = 1,663 that mean is tcalculate > ttable (5,354 > 1,663). H0 is rejcted and H1 is accepted, which means the effect is significant.There is a direct effect of leadership on the performance of β42 = -0,007 with mean tcalculate = -0,080. and ttable (α = 0,05) = 1,663 wich mean tcalculate < ttable (-0,080 < 1,663), so that H0 is accepted and H1 is rejected, which means the effect is not significant.There is a direct effect of organizational culture on the performance of β43 = 0,456 which mean tcalculate = 4,807. And ttable (α = 0,05) = 1,663 that mean tcalculate > ttable (4,807 > 1,663), this H0 is rejected and H1 is accepted, which means the effect is significant.There is a direct effect of organizational culture on employee motivation at β31 = 0,474 which mean tcalculate = 5,508. and ttable (α = 0,05) = 1,663 yang berarti tcalculate > ttable (5,508 > 1,663), So that mean H0 is rejected and H1 is accepted, which means the effect is significant.There is a direct effect of leadership on job motivation for β32 = 0,389 which mean tcalculate = 4,520. and ttable (α = 0,05) = 1,663 that means tcalculate > ttable (4,520 > 1,663), so that mean H0 is rejected and H1 is accepted, which means the effect is significant.Based on the above it can be concluded that employee performance can be improved through organizational culture and work motivation .Keyword: organization culture; leadership, motivation, employee performance